Brucella osteoarthritis: recent progress and future directions - Chen, Jinlei; Zhi, Feijie; Zhao, Guanghai; Su, Mengru; Geng, Hao; Song, Wei; Chu, Yuefeng; Zhang, Haihong (Frontiers in Microbiology, 2025)
Brucellosis is a common zoonosis, and Brucella osteoarthritis is the most common chronic complication of brucellosis. Development of brucellosis osteoarthritis involves multiple organs, tissues, and cells. Brucella grows and multiplies in intrinsic cells of the skeleton, including osteoblasts, osteocyte and osteoclasts, which results in sustained release of bacteria that leads to exacerbation of the immune response. Concurrently, activation of the immune system caused by invasion with Brucella may affect the dynamic balance of the skeleton. A variety of in vitro and in vivo models have been employed to study Brucella osteoarthritis, such as using bone marrow-derived macrophages to establish cell models and mice to develop animal models of Brucella osteoarthritis. However, limited studies on the molecular pathological mechanisms of Brucella osteoarthritis have been performed and inadequate animal models have been developed due to the challenging parameters of Brucella research. This paper reviews recent advances in the clinical features, molecular pathological mechanisms, and animal models of Brucella osteoarticular infections. This review underscores the complexity of the pathogenesis of Brucella osteoarticular infections and highlights inflammation as a contributing factor to bone loss caused by Brucella. Additionally, the significant proliferation of Brucella in skeletal resident cells also is an important factor leading to bone loss. A deeper understanding of the molecular pathological mechanism of Brucella osteoarthrosis and their animal models could provide robust support for the prevention and treatment of Brucella osteoarticular disease.